Subsidies for Regional Networks: Measurable Effects for Regional Development? - Diller, Christian; Nischwitz, Guido; Kreutz, Benedict (Raumforschung und Raumordnung | Spatial Research and Planning, 2014)
The change of paradigm of the policy for rural regions towards cooperative and actor-orientated regional development nowadays is hardly doubted. Nevertheless there are few findings on the effectivity of these subsidiaries. Presented in this article is the result of a nation-wide regional statistical analysis to the correlation of the support-programmes for cooperative regional development on one hand and established regional development indicators und the other hand. The distinctive feature to other analyses is the simultaneous analysis of several programmes supported by several political departements over a longer period. The result is obvious: in fact, effects for the regional development are not commensurable. This remarkable finding should give impulses for the enhancements of the instruments of rural development.
Keywords: Regional development; Support programmes; Regional networks; Effects; Efficiency